Methods of Organizing Tourism Routes and Routes in the Fergana Region (Journal of Architectural Design, 2022)
In this article, we develop recommendations for organizing tourism routes to architectural monuments in the regions of Fergana region and identifying their problems. Introducing our historical monuments to the world, as well as developing internal and external tourism by improving tourism routes in our republic, identifying problems and making practical suggestions